Utilization of Google Earth Engine in Monitoring and Estimating Carbon Stock of Simeulue Coral Reefs - Muhammad Taufik Rahmadi; Eni Yuniastuti; Tengku Gilang Pradana; Meilinda Suriani Harefa; M Rizky Pratama Ginting; Ayu Suciani (JPG (Jurnal Pendidikan Geografi), 2026)
Coral reef ecosystems are coastal ecosystems that have high productivity and play an important role in the absorption and storage of blue carbon and support biodiversity and the welfare of coastal communities. But the decline in coral reef ecosystem area due to anthropogenic pressure and climate change demands efficient and effective monitoring based on spatial data. This study aims to map the estimated carbon stock of coral reef ecosystems in Simeulue Regency based on Google Earth Engine using Sentinel-2A imagery. The analysis process includes atmospheric correction, supervised land cover classification, and extraction of biophysical parameters, as well as the development of a regression model of carbon stock estimation validated with field data. The results of the study show that the total area of coral reef ecosystems in Simeulue is 24,524.92 Ha with an estimated average carbon stock of 1,121.21gC/ha. Model validation resulted in a determination efficiency (R2) of 0.87 and an RMSE of 96 gC/ha. These results show a high level of accuracy on a regional scale. These findings confirm the potential of Google Earth Engine as an automatic, effective, and replicative carbon monitoring solution for coral reef ecosystems, as well as being used as input for sustainable conservation policy-making.